TADRIS AL-IMLA' BI AL-'ARABIYAH LI AL-NATHIQIN BI GHAIRIHA MUSYKILATUHU WA HULULUHU - Fatkhul Ulum; Enung Mariah; Enung Mariah (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2017)
Non-Arabic speakers find some problems during their Arabic learning, including spelling. The study limited these problems to the following matters: definition, dictation rules, and the accompanying difficulties. This study is a simple attempt to examine the solutions to these difficulties to improve the level of students' absorption of dictation. This study also addresses the causes of spelling errors. These errors may be attributed to the student, or to the teacher, or to the characteristics of the language itself. In light of these reasons, this study attempts to identify some methods to correct them. The researcher recommends not to adhere to one method on a continuous basis, but rather to combine the different methods, as the teacher deems appropriate, and achieve the purpose of the spelling subject.